2011
DOI: 10.1111/j.1462-2920.2011.02627.x
|View full text |Cite
|
Sign up to set email alerts
|

Ecological and evolutive implications of bacterial defences against predators

Abstract: SummaryBacterial communities are often heavily consumed by microfaunal predators, such as protozoa and nematodes. Predation is an important cause of mortality and determines the structure and activity of microbial communities in both terrestrial and aquatic ecosystems, and bacteria evolved various defence mechanisms helping them to resist predation. In this review, I summarize known antipredator defence strategies and their regulation, and explore their importance for bacterial fitness in various environmental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
179
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 218 publications
(185 citation statements)
references
References 145 publications
(228 reference statements)
4
179
0
2
Order By: Relevance
“…This result is confirmed by the work of Salcher et al (2005), in which they found a cluster of beta-Proteobacteria (BET3-446) and species of the genus Caulobacter, belonging to alpha-Proteobacteria, associated in aggregates as a consequence of increased nanoflagellates' abundance. Therefore, after the appearance of HNFs, changes in the interactions between alpha-and beta-Proteobacteria were observed, suggesting that the aggregation of bacteria in microcolonies could be a defense mechanism against predation (Matz & J€ urgens 2003;Jousset 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This result is confirmed by the work of Salcher et al (2005), in which they found a cluster of beta-Proteobacteria (BET3-446) and species of the genus Caulobacter, belonging to alpha-Proteobacteria, associated in aggregates as a consequence of increased nanoflagellates' abundance. Therefore, after the appearance of HNFs, changes in the interactions between alpha-and beta-Proteobacteria were observed, suggesting that the aggregation of bacteria in microcolonies could be a defense mechanism against predation (Matz & J€ urgens 2003;Jousset 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Most of the bacterioplankton cells of both marine and freshwater environments are small in size (volume < 0.03 mm 3 ). However, the numerically predominant fractions in aquatic environments under high grazing pressure are represented by ultramicrobacteria (volume < 0.001 mm 3 ) or large filaments (volume > 1 mm 3 ; Hahn et al 2003;Justice et al 2008;Jousset 2012). HNF grazing on bacteria is size-selective with a preference for medium-sized bacteria (Chrzanowski & Simek 1990;Gonz alez et al 1990;Simek & Chrzanowski 1992;Gonz alez 1996;Gl€ ucksman et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…[16,19,20], but see [21]), or constitute a cost that potentially impacts other cooperative behaviours (e.g. resource access and sharing, quorum sensing [19,22,23]). Such costs may differ between individuals adopting different social behaviours, and include energy or time committed to defence or resistance (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Third, natural enemies may select for resistance that has pleiotropic and epistatic consequences on cooperation [23], or resistance that promotes the emergence of diversity generating mechanisms influencing cooperation. For example, viruses may select for higher mutation rates in certain bacterial populations [23,33] (but see [34]), which could decrease relatedness and favour the emergence of intermediate phenotypes with varying levels of investment in cooperation [12].…”
Section: Introductionmentioning
confidence: 99%
“…Most soil protists are known to be key predators of bacteria and can shape bacterial communities by selective feeding (Griffiths et al 1999;Bonkowski & Brandt 2002;Rosenberg et al 2009;Glücksman et al 2010). Reaching suitable prey is very energy consuming (Jousset 2012). Thus, sensing their prey over long distances in the porous soil matrix would be very beneficial for protists.…”
Section: Protists-bacteriamentioning
confidence: 99%